Design of multi-carrier MIMO radar array for DOA estimation - Ulrich, Michael; Yinglai Yang; Bin Yang (2017 25th European Signal Processing Conference (EUSIPCO), 2017)
Multi-carrier (MC) multiple-input multiple-output (MIMO) radar offers an additional degree of freedom in the array optimization through the carrier frequencies. In this paper, we study the MC-MIMO array optimization with respect to the direction of arrival (DOA) estimation based on the Cramer-Rao bound (CRB). In particular, we choose the transmit and receive antenna positions as well as the carrier frequencies to minimize the single-target CRB subject to a constraint of the peak sidelobe level. A genetic algorithm is used to solve the problem and numerical examples demonstrate the superiority of our approach over both single-carrier MIMO radar and existing design rules.